The statute of tonal music in Susanne Langer - Lopes de Azevedo Júnior, Ivânio (2020)
This article aims to understand in terms of music, for Susanne Langer, interpreted in the light of a Symbolic Forms Philosophy. This expression, in turn, is a project or theoretical program of its master, Ernst Cassirer. A theory of art that Langer proposes in Philosophy in the New Key and in Feeling and Form is thought to be a continuity of Cassirer’s critique of culture, an idea based on the conception that once the need for symbolism has been demonstrated (function without which there is no culture), it is up to philosophy to understand and follow the historical development of the modes of manifestation of the Spirit. The Music, while the most abstract of the arts, is a particular mode of symbolism, whose maturity is its internal way of transmitting in what we now call tonal music. The tonalism is the stage in which music reaches its older age only because it has been able to operate from the laws of execution, thus being the result of a long process of constitution of the musical form.